1998
DOI: 10.1007/bf03038507
|View full text |Cite
|
Sign up to set email alerts
|

Is axillary dissection further required in clinically node negative breast cancer?

Abstract: Definitive radiotherapy of the axilla is a valid treatment option for patients without palpable axillary nodes with the potential advantage of being less cost intensive and better tolerated. If the indication for systemic therapy is no more dependent on the axillary status, axillary dissection may be replaced by axillary radiotherapy. In small tumors without risk factors and without indication for systemic therapy, SLND seems to be the best treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 101 publications
1
0
0
2
Order By: Relevance
“…As mentioned, older age is a main risk factor of vascular diseases, such as hypertension, which has been associated with lymphedema . These observations are supported by data from this current study, which observed a moderate correlation between age and vascular comorbidities (Spearman correlation coefficient, 0.48; P < .001) (eTable 1 in the Supplement), which encompassed the diagnoses of hypertension, hypercholesterolemia, and diabetes . High cholesterol levels have been mechanistically associated with the degeneration of lymphatic vessels, which has led to decreased lymphatic transport, increased leakiness, and increased edema .…”
Section: Discussionsupporting
confidence: 86%
“…As mentioned, older age is a main risk factor of vascular diseases, such as hypertension, which has been associated with lymphedema . These observations are supported by data from this current study, which observed a moderate correlation between age and vascular comorbidities (Spearman correlation coefficient, 0.48; P < .001) (eTable 1 in the Supplement), which encompassed the diagnoses of hypertension, hypercholesterolemia, and diabetes . High cholesterol levels have been mechanistically associated with the degeneration of lymphatic vessels, which has led to decreased lymphatic transport, increased leakiness, and increased edema .…”
Section: Discussionsupporting
confidence: 86%
“…1500 (90% Power) Signifikanzniveau erreichen [26]. Klinisch wäre dies jedoch nicht relevant [4,6], weil aufgrund der hohen p-Werte im tumorfreien und Gesamtüberleben auch bei einer solch großen Fallzahl kein Unterschied zu erwarten wäre. Sogar bei völlig unbehandelter Axilla konnte kein Einfluss auf das Überleben nachgewiesen werden [3,33,36), wobei dann allerdings in ca.…”
Section: Diskussionunclassified
“…In ebenfalls elf Arbeiten wurden die Ergebnisse lediglich nicht aktuarisch ("crude") ausgewertet [5,24,72,77,81,128,132,144,150,151,153]. In zwei Arbeiten [22,25] Table 2. Actuarial analysis of the data in Figure 1 according to the Kaplan-Meier method.…”
Section: Qualitätsanalyse Der Zeitschrift "Strahlentherapie Und Onkolunclassified